A new way of living: West Side Story, street dance and the New York musical. (22nd January 2016) - Shearer, Martha
Abstract : New York neighbourhoods had been prominent settings in studio-era Hollywood musicals, where street-dance sequences would be used to express the close social ties of such communities. However, as the postwar period progressed, 'blighted' urban neighbourhoods would become the site of both vigorous public debate and dramatic physical transformation in the form of 'urban renewal'. This meant that the musical's established modes of urban representation were being challenged by the impact of New York's postwar transformation and the increasing prominence of urban decline in public discourse. This essay both situates West Side Story in traditions of urban representation, particularly street dances, in Hollywood musicals and examines the film as a story of the West Side. I argue that the film is important and distinctive because it exists at an intersection of postwar crises affecting both the film industry and American cities. I combine textual analysis with production history and urban history to argue that the film's tensions between style and subject were an effect of its urban context, especially the impact of urban renewal in New York. I focus in particular on the film's Prologue, a lengthy balletic street dance sequence shot on location in a New York urban renewal area. I suggest that in its explicit attention to contemporary urban issues, West Side Story brings to the surface assumptions about cities that had structured earlier musicals and indicates the representational challenges the genre was facing in the 1960s.